Role of Neutrophil-to-Lymphocyte Ratio as a Predictor of Systemic Inflammatory Response Syndrome in Blunt Abdominal Trauma Following Emergency Laparotomy in Sanglah General Hospital, Denpasar - Purnamantara, I Made Dwi; Wiargitha, I Ketut; Mahadewa, Tjok Gede Bagus (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Abdominal trauma, both blunt and penetrating abdominal trauma, is the third most common trauma, which is about 10% after head trauma (30%) and chest trauma (20%). Trauma has an influence on the balance of the immune system. The excessive inflammatory response can trigger systemic inflammatory response syndrome (SIRS). The ratio of neutrophils to lymphocytes acts as a marker of the inflammatory response in both surgical and non-surgical patients. AIM: The purpose of the study was to predict the incidence of SIRS using neutrophils-to-lymphocytes ratio (NLR) in patients with blunt abdominal trauma undergoing emergency laparotomy. METHODS: This study is an observational analytic study with a prospective design which was carried out at the emergency room, intensive care unit, Sanglah Hospital, Denpasar, Surgery for 1 year from January 2019 to December 2019, involving 59 research subjects with the consecutive sampling method who is met the inclusion and exclusion criteria. RESULTS: The area under the curve value obtained an NLR sensitivity of 87.1% with a cutoff point of 5.25. In the path analysis, it was found that NLR was the dominant factor and had a positive effect of 43.9% (p < 0.001) on SIRS. CONCLUSION: NLR is expected to be used as a reference to predict the incidence of SIRS in blunt abdominal trauma following laparotomy emergency.